An Experimental Investigation Of Pool Boiling At Atmospheric Pressure (Daffodil International University Journal of Science and Technology, 2011)
This paper deals with an experimental investigation of pool boiling of water and methanol at atmospheric pressure from small horizontal heat sources. The heat sources are inserted into the copper tube submerged in a laterally-confined, finite pool of liquid. The saturated pool boiling heat transfer characteristics and the critical heat flux (CHF) condition were determined in the experiments. In the experiment, an attempt has been made to estimate the heat flux for pool boiling of Water and Methanol at atmospheric pressure. An indoor experiment was conducted to measure (i) the heat flux of water and methanol, (ii) the temperature of the working fluids, (iii) the wall superheat temperatures, (iv) the temperatures at the bottom and side of the pot, (v) time required to be superheated at definite time intervals for a given heat input. The heat input has been varied by changing the voltage with the help of a voltage regulator. A regression analysis has been performed by using the experimental data in the correlation of Rohsenow for pool boiling. Keywords: Pool Boiling; Heat Flux; Wall Superheat; Correlation. DOI: http://dx.doi.org/10.3329/diujst.v6i1.9337 DIUJST 2011; 6(1): 80-86